Sabun Cair Antiseptik Sari Air Kulit Buah Salak (Salacca zalacca) - Gunawan, Muhammad; Fatimah, Cut; Panjaitan, Sariatmaja (Journal of Pharmaceutical and Health Research, 2024)
In addition to removing dirt that sticks to the skin, skin wash soap also functions as an antiseptic to ward off skin diseases caused by germs, many antiseptic soaps on the market contain synthetic antibacterials but often have negative side effects. Therefore, it is important to make soap with natural ingredients. For example, salak (Salacca zalacca) fruit peel contains saponin and polyphenol compounds that are antibacterial. To test the antibacterial activity and make liquid soap containing salak fruit peel juice as a cleanser and antibacterial, this study conducted phytochemical screening on salak fruit peel. The research stages include, phytochemical screening of salak fruit peel, liquid soap formulation with 10%, 20%, and 30% salak fruit peel juice (SKBS), liquid soap assessment related to stability, foam height, pH, irritation, and liking test. Antibacterial activity test against germs from volunteer hand wash water specimens against Escherichia coli, and Staphylococcus aureus bacteria. The results showed that salak fruit peel juice can be used to make liquid soap that meets physical quality standards because it contains alkaloids, flavonoids, tannins, saponins, steroids/triterpenoids, and glycosides. The strongest antibacterial activity with inhibition diameters against Staphylococcus aureus (18.63 ± 0.33) mm and Escherichia coli (16.17 ± 0.33) mm) made 20% SKBS liquid soap the best choice, which was determined by the results of the study.